Live mucosal vaccination stimulates potent protection via varied CD4+ and CD8+ T cell subsets against wild-type Brucella melitensis 16M challenge - Goodwin, Zakia I.; Yang, Xinghong; Hoffman, Carol; Pascual, David W. (Frontiers in Immunology, 2022)
Re-emerging zoonotic pathogen Brucella spp continues to impact developing countries and persists in expanding populations of wildlife species in the US, constantly threatening reinfection of our domestic herds. The development of improved animal and human vaccines remains a priority. In this study, immunity to a novel live attenuated B. melitensis strain, termed znBM-mC, was characterized. An oral prime, intranasal (IN) boost strategy conferred exquisite protection against pulmonary challenge with wild-type (wt) B. melitensis providing nearly complete protection in the lungs and spleens from brucellae colonization. Vaccination with znBM-mC showed an IFN-γ+ CD8+ T cell bias in the lungs as opposed to Rev 1-vaccinated mice showing IFN-γ+ CD4+ T cell inclination. Lung CD4+ and CD8+ effector memory T cells (TEMs) increased over 200-fold; and lung CD4+ and CD8+ resident memory T cells (TRMs) increased over 250- and 150-fold, respectively. These T cells served as the primary producers of IFN-γ in the lungs, which was essential for vaccine clearance and the predominant cytokine generated pre-and post-challenge with wt B. melitensis 16M; znBM-mC growth could not be arrested in IFN-γ-/- mice. Increases in lung TNF-α and IL-17 were also induced with IL-17 being mostly derived from CD4+ T cells. Vaccination of CD4-/-, CD8-/-, and B6 mice with znBM-mC conferred full protection in the lungs and spleens post-pulmonary challenge with virulent B. melitensis; vaccination of IL-17-/- mice resulted in protection of the lungs, but not the spleen. These data demonstrate the efficacy of mucosal vaccine administration for generation of protective memory T cells against wt B. melitensis.